Unintended Consequences of Human Actions - Ermolaeva, Elena; Ross, Jessica (Hamilton Books, 2012)
Using a mixed-method approach, Unintended Consequences of Human Actions documents a wide range of unintended and unanticipated consequences of human actions. The major message is the urgent need to review a range of possible outcomes of human actions. During these fragile times 'looking down the road' has become imperative.